Controllable self-assembly of thiophene-based π-conjugated molecule and further construction of pillar[5]arene-based host-guest white-light emission system - Zhong, Haibo; Li, Liang; Zhu, Shajun; Wang, Yang (Frontiers in Chemistry, 2022)
Photoluminescence materials have been widely applied in biological imaging and sensing, anti-counterfeiting, light-emitting diodes, logic gates et al. The fabrication of luminescent materials with adjustable emission color by self-assembly of π-conjugated molecules has attracted particular attention. In this study, we designed and synthesized a thiophene-based α-cyanostyrene-derivative (TPPA), then investigate its self-assembly morphology and fluorescence emission under different organic solvents, different proportions of H2O/THF (DMSO) mixture and different pH conditions by UV, FL and SEM images. It was found that TPPA formed nanoparticles by self-assembly in organic solvent (THF or DMSO), accompanied by strong fluorescence emission. However, with the increase of water ratio, the fluorescence intensity decreased accompany with red shift, and the self-assembly morphology changed from nanoparticles to fibers. More interestingly, when pillar[5]arene (P5) was added to form host-guest complex with TPPA, white light emission could be successfully constructed when the ratio of TPPA to P5 was 1:20 and THF to water was 19:1.